2018
DOI: 10.1080/14737140.2018.1469980
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy for advanced renal cell carcinoma

Abstract: Locally advanced, non-metastatic renal cell carcinoma (RCC) is conventionally managed with surgery. However, patients are at a high risk of RCC recurrence and have poor survival outcomes. An effective adjuvant systemic treatment is needed to improve on these outcomes. Targeted molecular and immune-based therapies have been investigated, or are under investigation, but their role in this setting remains unclear. Areas covered: A comprehensive search of PubMed and ClinicalTrials.gov was performed for relevant li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…To improve these results, the role of adjuvant treatments after surgery is being investigated to eliminate possible foci of clinically undetectable micrometastases [7]. Several adjuvant strategies, including cytokine therapy, radiotherapy, and hormone therapy, have been explored to decrease the rate of relapse, but none have been successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve these results, the role of adjuvant treatments after surgery is being investigated to eliminate possible foci of clinically undetectable micrometastases [7]. Several adjuvant strategies, including cytokine therapy, radiotherapy, and hormone therapy, have been explored to decrease the rate of relapse, but none have been successful.…”
Section: Introductionmentioning
confidence: 99%
“…Several adjuvant strategies, including cytokine therapy, radiotherapy, and hormone therapy, have been explored to decrease the rate of relapse, but none have been successful. The proven efficacy of antiangiogenic therapies, including the vascular endothelial growth factor (VEGF) pathway inhibitors in patients with metastatic renalcell carcinoma (mRCC) supports the evaluation of these drugs as adjuvant therapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, all studies considered in our analysis adopted different selection modalities with a not negligible heterogeneity in terms of tumour stages, risk of recurrence and tumour subtypes included. In fact, the S-TRAC trial enrolled a higher-risk population and the study protocol had important restrictions on histologic subtypes compared with ASSURE, something that could have played an important role in the highest DFS benefit observed in S-TRAC (9,10). More specifically, one-third of patients of the ASSURE trial had low-risk tumours-pT1 and pT2-and the ATLAS and the PROTECT studies included an important proportion of these patients (11% and 14%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, adjuvant treatment in RCC is still a problematic issue despite several adjuvant therapies have been tested in an attempt to improve clinical outcomes for RCC patients (9). Indeed, none of the compounds evaluated in this field have shown a convincing clinical benefit justifying an inclusion in clinical practice (10).…”
Section: Review Article On Update On Molecular Classification and Indmentioning
confidence: 99%
“…Clinical trials looking at the overall survival benefit and toxicity of sunitinib, pazopanib, and axitinib have shown no improvement in overall survival and an increase in toxicity. 27 Only one study with sunitinib conducted during the modern age of RCC care has shown an increase in progression-free survival (PFS), but also showed a much higher frequency of grade 3 and grade 4 adverse events. 28…”
Section: Treatment Of Localized Diseasementioning
confidence: 99%